2015
DOI: 10.15561/18189172.2015.1103
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of upper limb’s condition of women with post mastectomy syndrome with the help of problem-oriented program of physical rehabilitation

Abstract: Abstract. Purpose: to determine effectiveness of problem-oriented program of women's physical rehabilitation with post mastectomy syndrome in improvement of upper limb's functional state. Material: 50 women with early symptoms of post mastectomy syndrome at stationary rehabilitation stage, who underwent radical mastectomy by Madden were involved in the research. Testing of movement amplitude in shoulder joint, swelling of upper limb and muscular strength of hand's flexors was conducted on 2 nd day after surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…Окремі вчені створювали авторську програму з прицілом на досягнення мети і назвали її проблемноорієнтованою. За твердженням науковців «добиралися строго індивідуально засоби, форми і методи фізичної реабілітації, які найефективніше допоможуть вирішити завдання та досягти поставленої мети» [16]. З цитованого випливає, що заняття фактично проводилися не за однією, а різними програмами.…”
Section: результати дослідження та їх обговоренняunclassified
“…Окремі вчені створювали авторську програму з прицілом на досягнення мети і назвали її проблемноорієнтованою. За твердженням науковців «добиралися строго індивідуально засоби, форми і методи фізичної реабілітації, які найефективніше допоможуть вирішити завдання та досягти поставленої мети» [16]. З цитованого випливає, що заняття фактично проводилися не за однією, а різними програмами.…”
Section: результати дослідження та їх обговоренняunclassified
“…Previous research [23,24] has clearly shown that all patients who have undergone radical treatment for breast cancer have an extreme need for physical and psychological rehabilitation. However, the theoretical analysis of the available papers in the scientific literature suggests that the issues related to physical rehabilitation for patients with PMS have not been completely resolved.…”
Section: Introductionmentioning
confidence: 99%
“…PMS is expressed in such symptoms as lymphostasis, weakening of muscular strength, restriction of movements' amplitude in shoulder joint, disordering of sensitivity, vegetative trophy disorders of upper limb and negative psycho-emotional effects. Advanced randomized researches (Carayol et al, 2012;Lin et al, 2012;Mehnert et al, 2011;Schmitz et al, 2012;Briskin & Odinets, 2015) clearly show that all of the patients, who underwent radical treatment for breast cancer, extremely needed physical and psychological rehabilitation, which adequate conducting not only contributes to a noticeable improvement in health and physical condition, but also significantly improves the quality of life. The stressful factors are the detecting of malignancy, the presence of public understanding of the absence of the recovery possibility, a high percentage of deaths, possible surgery, radiation and chemotherapy which are closely related to somatic discomfort (Smoot et al, 2009;Park et al, 2012;Rashid et al, 2012;).…”
Section: Introductionmentioning
confidence: 99%